2006
DOI: 10.1152/ajpcell.00351.2005
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase activation and shedding with HAI-1 is induced by steroid sex hormones in human prostate cancer cells, but not in breast cancer cells

Abstract: . Matriptase activation and shedding with HAI-1 is induced by steroid sex hormones in human prostate cancer cells, but not in breast cancer cells. Am J Physiol Cell Physiol 291: C40 -C49, 2006. First published February 8, 2006 doi:10.1152/ajpcell.00351.2005.-Matriptase and its cognate inhibitor, hepatocyte growth factor activator inhibitor-1 (HAI-1), have been implicated in carcinoma onset and malignant progression. However, the pathological mechanisms of matriptase activation are not defined. Steroid sex hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 58 publications
4
43
0
Order By: Relevance
“…Among them, matriptase has been focused on because it plays crucial roles in carcinogenesis and cancer cell invasion including prostate cancer (9)(10)(11)(12). In prostate cancer cells, androgens can induce matriptase activation and shedding (13). However, the molecular mechanism through which androgens induce matriptase activation and whether the androgen-induced proteolytic cascade plays a role in prostate cancer progression and metastasis are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, matriptase has been focused on because it plays crucial roles in carcinogenesis and cancer cell invasion including prostate cancer (9)(10)(11)(12). In prostate cancer cells, androgens can induce matriptase activation and shedding (13). However, the molecular mechanism through which androgens induce matriptase activation and whether the androgen-induced proteolytic cascade plays a role in prostate cancer progression and metastasis are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Matriptase autoactivation is induced by an array of structurally unrelated molecules in a relatively cell type-specific manner. For example, we have shown that matriptase activation is induced by the lysophospholipid sphingosine 1-phosphate in mammary epithelial cells (5) and by androgens in LNCaP prostate cancer cells (18). Although matriptase expression is observed in almost all epithelial tissues in vivo, matriptase activation is limited (42).…”
mentioning
confidence: 99%
“…This activation step converts the singlechain matriptase zymogen to a two-chain active form (4,31). Matriptase zymogen activation is controlled by exogenous stimuli (5,18,20) and dependent upon assembly of the activation complex (20). Matriptase autoactivation is induced by an array of structurally unrelated molecules in a relatively cell type-specific manner.…”
mentioning
confidence: 99%
“…tion linked to spatial redistribution include suramin and androgens in prostate cancer cells (18). The ability of the matriptase zymogen to become activated and presented on the cell surface may depend on the direct physical interaction with its cognate Kunitz-type serine protease inhibitor HAI-1 ( Figure 1B).…”
mentioning
confidence: 99%